Electronic excitations and correlations in quantum bars - Kuzmenko, I.; Gredeskul, S.; Kikoin, K.; Avishai, Y. (Физика низких температур, 2002)
The spectrum of boson fields and two-point correlators are analyzed in a quantum bar system (a superlattice formed by two crossed interacting arrays of quantum wires), with a short-range interwire interaction. The standard bosonization procedure is shown to be valid, within the two-wave approximation. The system behaves as a sliding Luttinger liquid in the vicinity of the Γ point, but its spectral and correlation characteristics have either 1D or 2D nature depending on the direction of the wave vector in the rest of the Brillouin zone. Due to the interwire interaction, unperturbed states propagating along the two arrays of wires are always mixed, and the transverse components of the correlation functions do not vanish. This mixing is especially strong around the diagonals of the Brillouin zone, where the transverse correlators have the same order of magnitude as the longitudinal ones.